A five-year strategic financial plan for Century Pacific Food, Inc - Busante, Annjaneth V., Cairme, Joyce Ann T., Francisco, Via Joyce O., Mandoh, George Luis B., Risch, Clyde Devon. 4 0 16; 5 (2024)
Executive Summary Century Pacific Food, Inc. is under the food and beverage industry which operates primarily in the buying, selling, processing, canning, packaging, and manufacturing of various food products, including fish, seafood, livestock, fruits, and vegetables. As of June 30, 2024, Century Pacific Food, Inc. is a 65.5% owned subsidiary of Century Pacific Group, Inc. (CPGI), the ultimate parent company, which is also registered with the SEC and based in the Philippines. Century Pacific Food, Inc. has a strong competitive position with high rivalry among competing firms, the entity is crowded with both local and international competitors, such as San Miguel Food and Beverage, Inc., Republic Flour Mills, Inc., Pepsi- Cola Products Philippines, Inc., and Liberty Flour Mills, Inc., all of which have strong brand recognition, significant financial resources, and extensive distribution networks. This shows that the century pacific foods inc. needs to sustain its competitive advantage to maintain a good market standing. Based on financial statements, the entity is facing low inventory turnover, high cost of sales, and declining profitability. The financial analysis highlights the need for improved inventory management and cost strategies to sustain its market position. In 2023, inflation increased input costs further strained profitability, though the entity's focus on affordability and product innovation helped mitigate these risks. The recommended strategy the entity can use based on the various matrices and strategy formulation tools is Improve Inventory Forecasting, Demand Planning, and Marketing Strategy. CNPF is facing substantial difficulties with its inventory management practices, resulting in high carrying costs, excessive stock levels, and poor inventory turnover. These inefficiencies are diminishing profitability and hindering the entity's ability to generate optimal returns from its investments. CNPF's main issue lies in its overstocking of certain product lines, leading to higher inventory holding costs, including storage, insurance, and handling expenses. This situation worsens as unsold products remain in the inventory for prolonged periods, tying up capital and increasing the risk of obsolescence. To resolve this problem, the Entity needs to implement a comprehensive inventory optimization strategy. This strategy will focus on enhancing inventory turnover by better aligning stock levels with actual market demand, reducing excess inventory, and minimizing the carrying costs associated with slow-moving products. In summary, the proposed inventory optimization strategy is essential for addressing CNPF's inventory management challenges. It will lead to enhanced profitability, improved operational efficiency, and long-term financial stability. By adopting these recommendations, CNPF will position itself to maintain its competitive advantage and achieve sustainable growth in the years ahead.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2